Effect of Technostress on Boreout Syndrome Among Municipal Workers: A PLS-SEM Approach - Sánchez Vásquez, Krisbell Mariella Esther (2025)
This study examines the effect of technostress on boreout syndrome among municipal workers in Lambayeque, Peru, addressing a significant gap in the literature regarding the relationship between technological stressors and workplace disengagement. Using a quantitative, correlational, non- experimental design, data were collected from 300 municipal employees through validated scales measuring technostress (RED-TIC) and boreout syndrome. Structural equation modeling with partial least squares (PLS-SEM) was employed to test the hypothesized relationships. Contrary to theoretical expectations, results revealed a significant negative relationship between technostress and boreout syndrome (β = −0.584; p < 0.001), with a large effect size (f² = 0.519). This paradoxical finding suggests that technological demands may serve as cognitive activators that protect against workplace boredom and disengagement rather than precipitating it. The inverse association challenges conventional stress theories and indicates that appropriately calibrated technological challenges could function as engagement catalysts in public sector environments. These findings have important implications for human resource management and organizational development, suggesting that technology integration strategies should focus on maintaining optimal stimulation levels rather than minimizing all forms of workplace stress. The study contributes to theoretical refinement of stress models in digital work contexts and provides empirical evidence for reconceptualizing the role of technological demands in preventing psychological disengagement. Limitations include the cross-sectional design and geographical specificity, indicating the need for longitudinal and cross-cultural research to validate these counterintuitive findings.